Analisis Sensitivitas Dan Spesifisitas COVID-19 Ag Rapid Test Terhadap PCR Test - Wisnu Murti; Dian Rachma Wijayanti; Wulan Fitriani Safari (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2022)
SARS-Cov-2 is the newest coronavirus caused Covid-19 which can infect human and pandemic, COVID-19 parameter testing can be done with serological tests used to detect antibody or antigen and also molecular test using PCR method. This research is aimed to compare the sensitivity and specificity between COVID-19 Ag rapid test and PCR test. This research is an analytical descriptive study with 421 samples were obtained from documentation study with probability systematic random sampling and by using secondary data taken from Laboratory Information System (LIS) at Siloam Hospitals Lippo Village Tangerang and the type of observational analytical research with cross sectional design. The analysis results show the sensitivity rate was 96.64%, specificity was 93.75%, PPV was 89.44%, NPV was 98.08%, LR (+) was 15.46, and LR (-) was 0.04. The conclusion of the research result, COVID-19 Ag rapid test is valid to be used as a diagnostic test because it has high rate of sensitivity and specificity according to WHO regulations.